Normal range estimation for repeated immunologic measures - Taylor, J M; Cumberland, W G; Meng, X; Giorgi, J V (Clinical and Diagnostic Laboratory Immunology, 1996)
Services CVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue CVI About CVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy CVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1556-6811 Online ISSN: 1556-679X Copyright © 2014 by the American Society for Microbiology. For an alternate route to CVI .asm.org, visit: CVI